2014
DOI: 10.1259/bjr.20130630
|View full text |Cite
|
Sign up to set email alerts
|

Complications of rotator cuff surgery—the role of post-operative imaging in patient care

Abstract: When pain or disability occurs after rotator cuff surgery, post-operative imaging is frequently performed. Post-operative complications and expected post-operative imaging findings in the shoulder are presented, with a focus on MRI, MR arthrography (MRA) and CT arthrography. MR and CT techniques are available to reduce image degradation secondary to surgical distortions of native anatomy and implant-related artefacts and to define complications after rotator cuff surgery. A useful approach to image the shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…MARS imaging can successfully be performed at the shoulder . However, since the shoulder is not located in the isocenter of the main magnetic field but peripherally with a more inhomogeneous magnetic field, severe inhomogeneity artifacts are encountered .…”
Section: Clinical Applicationmentioning
confidence: 99%
“…MARS imaging can successfully be performed at the shoulder . However, since the shoulder is not located in the isocenter of the main magnetic field but peripherally with a more inhomogeneous magnetic field, severe inhomogeneity artifacts are encountered .…”
Section: Clinical Applicationmentioning
confidence: 99%
“…6a-d) [5,30]. If displaced into the glenohumeral joint, suture anchors can also cause a locking sensation of the shoulder [4,5]. One case study found a suture anchor displaced into the acromioclavicular joint [29].…”
Section: Complications Of Rotator Cuff Repair On Mrimentioning
confidence: 99%
“…In the symptomatic patient after rotator cuff repair, the primary etiologies to consider include, but are not limited to, rotator cuff re-tear, impingement, and postoperative synovitis. Hardware dislodgement can also be an unexpected finding on imaging, which may cause significant pain and impairment [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11). 25 Partial and complete tearing of the proximal deltoid muscle may also occur in patients with chronic large rotator cuff tears related to attrition from spurring and hypertrophy of the greater tuberosity (►Fig. 12).…”
Section: Supraspinatusmentioning
confidence: 99%